A220 THE IMPACT OF DIABETES AND AGE ON PERFORMANCE OF NON-INVASIVE SERUM-BASED TESTS FOR PREDICTION OF ADVANCED FIBROSIS IN BIOPSY-PROVEN NAFLD. (21st February 2022) - Kosick, H M; Shengir, M; Adeyi, O; Sebastiani, G; Patel, K
Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is now a leading cause of end-stage liver disease. Advanced stage F3-4 fibrosis predicts liver-related mortality in NAFLD patients. Simple non-invasive serum-based tests (NIT) for F3-4 are limited by indeterminate scores, necessitating secondary tests or liver biopsy. Diagnostic NIT cut-offs may vary in NAFLD patients with diabetes mellitus (DM) and the elderly. Identifying appropriate thresholds in populations in which these tests can be applied will reduce indeterminates and facilitate their broader use. Aims: The aim of this study was to assess the impact of DM status and age on the performance of NIT for prediction of advanced fibrosis in patients with biopsy-proven NAFLD. Methods: Patients presenting to two Canadian tertiary care centers between 2010–2018 for liver biopsy to diagnose NAFLD were included in this study. NIT including NFS, FIB4, BARD, AST-to-platelet ratio index (APRI), and AST to ALT ratio (AST/ALT) were calculated for each patient using validated cut-offs. Results: 457 patients were included in this study. Mean age was 48.8±12.9 years, 56% male, mean BMI 32.3 ± 6.7kg/m 2, 69% with DM, and F3-4 prevalence 48%. Indeterminate rates for NIT were generally higher for older patients, with or without DM (27–49% and 37–52%, vs. 33–42% and 20–37%, respectively). FIB-4 and NFS both had high specificity >0.9 in DM patients <60 years (Table 1). There were no differences in AUROC for individual NITs between patients with and without DM, and those < 60 vs. ≥ 60, nor between individual NIT within these groups. Conclusions: DM status and age, ≥ 60 vs. < 60, do not appear to have a significant impact on diagnostic performance of serum-based NIT in our cohort. Older patients had higher indeterminate results and reduced specificity, but T2DM status and age did not appear to have an impact on rate of misclassified patients. Serum-based NIT thresholds need to be optimized for older patients to reduce indeterminates and improve specificity. Funding Agencies: None